Kinerja Layanan Administrasi Pelimpahan Porsi Jemaah Haji Reguler pada Kantor Wilayah Kementerian Agama, Sumatera Utara - Muhammad Hanbali Bakti; Nina Siti Salmaniah Siregar; Budi Hartono (Mahesa Research Center, 2023)
Hajj is one of the pillars of Islam and an annual worship carried out by Muslims around the world who have the istito'ah/ability (material, physical and scientific) to visit and carry out several worship activities in several places in Saudi Arabia or we often hear by the name of the season of Hajj or the month of Zulhijah. The current Hajj problems, coupled with the problems that arose during the Covid-19 pandemic, were handled by a system for delegating the portion of the Hajj which has become a benchmark for performance at the Regional Office of the Ministry of Religion of North Sumatra Province. This research was conducted using qualitative research methods. The results showed that the performance of the administrative service bureaucracy for the delegation of portions of regular pilgrims at the Regional Office of the Ministry of Religion of North Sumatra Province had met the service standards in accordance with the performance theory by Pollit & Bouckaert used in this study.